(3GdEOGQI GdeOQSjI aj dHfGf(B: (3eTcdGJ hMdhd ebJQMIs - (3jYbhH, Sgjds ((3HjQhJs (3GdgjFI GddHfGfjI ddYdhe GdJQHhjIs, 2001)
(3JJfGhd gPg GdOQGSI aj GdbSe GdChd efgG GdeaGgje GdeYGUQI GdeJYdbI HGdEOGQI GdeOQSjI, eJhbaI YfO GdbjGOI hGdGJLGgGJ GdJj aQVJ JZjjQkG aj OhQ GdeOjQ OGNd GdShQ hNGQLg, hGdJj COJ Edi RjGOI GdVZhW Ydjg(B. (3ceG jJfGhd gPG GdbSe eG TgOJg GdhdGjGJ GdeJMOI hcfOG hHQjWGfjG haQfSG hCSJQGdjG ef JZjQGJ aj HQGeL EYOGO GdeOjQjf hJOQjHge(B. (3hjNdU GdHGMK ef Pdc Edi JMOjO ehGUaGJ eOjQ GdeOQSI GdeYGUQ(B. (3CeG GdbSe GdKGfj agh eNUU dhGbY GdEOGQI GdeOQSjI aj dHfGf ef NdGd GSJYQGV hJMdjd GdHjGfGJ hGdeYWjGJ GdeJhGaQI Mhd Pdc(B. (3hCNjQkG JbOe GbJQGMGJ ChdjI dJWhjQ HQGeL GdEYOGO hGdJOQjH deOjQj GdeOGQS GdQSejI aj dHfGf, ceG JWQM HYV GdJhUjGJ ajeG jNU GdEOGQI GdJQHhjI hGdEOGQI GdeOQSjI Ydi CSGS Cf GdEOGQI GdeOQSjI gj LRA dG jJLRC ef GdEOGQI GdJQHhjI GdJj gj HOhQgG eJOGNdI eY GdEOGQI GdYGeI aj GdHdGO hYdi CSGS Cf GdeOjQ gh hcjd GdJZjjQ aj GdJQHjI(B.s
(3GdfhY (B: (3aUd aj cJGHs
Keywords: Gestion scolaire; School management; (3GdGOGQI GdeOQSjIs